Edição de performance e recital da sonata para cello e piano Op.24 nº1 de Helza Câmeu - Ana Paula Faria Ferreira (2005)
The present work is divided in two parts: (1) a recording of the Sonata opus 24 no. 1 by Helza Camêu, interpreted by the author of this work; and (2) an article presenting a brief biography of Helza Camêu, considerations about stylistic aspects of composers music, and an edition of the Sonata opus 24 no. 1 based in a structural,harmonic and stylistic analysis of the movements. The analysis also contribute to discuss technical aspects of the work. The prime aim of this work was divulging brazilian music for and specially, Helza Camêus Music.